THE IMPACT OF THE UNITED STATES SANCTIONS ONINTERNATIONAL RELATIONS (IUS LAW Journal, 2025)
This study aims to show the impact of the United States of America (the US) sanctions oninternational relations, principles of international law, and the countries targeted and not targetedby sanctions. Since sanctions are not issued by a legislative authority of the internationalcommunity, which constitutes a clear violation of the principles of international law, they maylead to the US having an impact on those countries and issuing potential questions of neocolonialism.Also, they can lead to creating alliances between countries that support sanctionsand others that reject them, which may result in the collapse of world peace. The effects of theUS sanctions go beyond the principles of personality and territoriality of law and affect thesovereign states recognized in international law, as well as the global economic and socialsystem, and the rights of peoples in the sanctioned countries. These sanctions may question thelegal principle that there is no crime or punishment without law.
Keywords: The United States, American sanctions, international law, sovereignty, international security, international alliances, public order